A Study on the Deterring Factors to Entrepreneurship among Graduates of Agriculture and Natural Resources: Case Study in Bushehr, Iran - Hedjazi, Yousef (Journal of Economics and Behavioral Studies, 2015)
The purpose of this research was to study deterring factors to entrepreneurship among graduates of agriculture and natural resources. A survey approach was used in this research. The statistical population included ninety eight graduates of agriculture and natural resources who are working in private or governmental business units in the province of Bushehr, Iran. A questionnaire was developed to interview the subjects of the study of which the validity and reliability were estimated based on the opinions of a panel of experts and Cronbach’s alpha coefficient respectively. The results indicated that among personality factors, low self-confidence and low spirit of independence were the most important deterring factors to entrepreneurship. The results also revealed that a weak relation between university and business environment, insufficient practical and theoretical education, high risk of investment in the agriculture, and legal and administrative restrictions were the most important environmentally deterring factors. Based on this research finding, male graduates had a higher spirit of opportunity recognition and independence than female graduates.